Genome studies at the PAG 2011 conference - Appels, R.; Adelson, D.; Moolhuijzen, Paula; Webster, H.; Barrero, R.; Bellgard, M. (2011)
The contents of the plenary lectures presented at the Plant and Animal Genome (PAG) meeting in January 2011 are summarized in order to provide some insights into the advances in plant, animal and microbe genome studies as they impact on our understanding of complex biological systems. The areas of biology covered include the dynamics of genome change, biological recognition processes and the new processes that underpin investment in science. This overview does not attempt to summarize the diversity of activities that are covered during the PAG through workshops, posters and the suppliers of cutting-edge technologies, but reviews major advances in specific research areas. © 2011 Springer-Verlag.